Electron Transfer Reactivity of Type Zero Pseudomonas aeruginosa Azurin - Lancaster, Kyle M. (2011)
Type zero copper is a hard-ligand analogue of the classical type 1 or blue site in copper proteins that function as electron transfer (ET) agents in photosynthesis and other biological processes. The EPR spectroscopic features of type zero Cu(II) are very similar to those of blue copper, although lacking the deep blue color, owing to the absence of thiolate ligation. We have measured the rates of intramolecular ET from the pulse radiolytically generated C3-C26 disulfide radical anion to the Cu(II) in both type zero C112D/M121L and type 2 C112D Pseudomonas aeruginosa azurins in pH 7.0 aqueous solutions between 8 and 45 °C. We also have obtained rate/temperature (10 to 30 °C) profiles for ET reactions between these mutants and the wild type azurin. Analysis of the rates and activation parameters for both intramolecular and intermolecular ET reactions indicates that the type zero copper reorganization energy falls in a range (0.9–1.1 eV) slightly above that for type 1 (0.7–0.8 eV), but substantially smaller than that for type 2 (> 2 eV), consistent with XAS and EXAFS data that reveal minimal type zero site reorientation during redox cycling.